1988
DOI: 10.1097/00000658-198804000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Use of Transfusion Therapy Perioperatively in Patients with Sickle Cell Hemoglobinopathies

Abstract: During the period of 1978 to 1986, 66 patients (31 men, 35 women) with a mean age of 28.4 years and various sickle cell hemoglobinopathies underwent 82 surgical procedures; 28 were emergencies. Fifty of the 66 patients had HbSS, 13/66 had HbSC, and 3/66 had HbS-thalassemia. All 66 patients received transfusions, although not for all procedures. In 48 patients, transfusion therapy was only administered preoperatively. Simple transfusions (1 to 10 units) were administered in 31 of 48 procedures. Exchange transfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…The authors of these studies therefore concluded that conservative treatment with simple transfusions to a target Hct level of less than 30 percent is the preferred choice. Other authors, however, have questioned the need for preoperative transfusion for all SCD patients 37‐39 . Recent studies suggest that SCD patients undergoing laparoscopic cholecystectomy without preoperative transfusion have comparable complication rates to those who have been transfused 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors of these studies therefore concluded that conservative treatment with simple transfusions to a target Hct level of less than 30 percent is the preferred choice. Other authors, however, have questioned the need for preoperative transfusion for all SCD patients 37‐39 . Recent studies suggest that SCD patients undergoing laparoscopic cholecystectomy without preoperative transfusion have comparable complication rates to those who have been transfused 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that patients with SCD have a higher incidence of postoperative morbidity and mortality than patients without hematologic abnormalities [4,12,13,15,19,20,22]. In one such study, the risk of postoperative complications in patients with SCD ranged from 7% to 32% [7].…”
mentioning
confidence: 99%
“…However, many clinicians practice successfully with minimal use of transfusions [4,5,12]. Nonrandomized comparisons of sickle cell patients undergoing minor procedures such as myringotomy and adenotonsillectomy have shown lower or equivalent complication rates in nontransfused patients [19].…”
mentioning
confidence: 99%
“…Patients with SCD are at risk for perioperative complications including ACS, renal failure, pain episodes, and stroke. Preoperative transfusions have been reported beneficial and are usually, but certainly not universally, recommended if the patient is to receive general anesthesia or is to have surgery on the posterior segment of the eye (23,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57). The optimal transfusion regimen, however, remains controversial.…”
Section: Surgerymentioning
confidence: 99%